KONTRIBUSI KHULAFAUR RASYIDIN TERHADAP SISTEM PENDIDIKAN ISLAM DAN IMPLIKASINYA BAGI MADRASAH - Afiyati, Fudla; Sugeng Listyo Prabowo (Najah Bestari, 2025)
Islamic education has strong historical roots since the era of the Khulafaur Rasyidin, where the education system began to develop in a structured manner and was oriented towards the formation of morals and the strengthening of religious knowledge. This study aims to analyze the contribution of the Khulafaur Rasyidin to the formation of the Islamic education system and its implications for the management of madrasas in the modern era. The method used is qualitative-descriptive with a library research approach through a review of relevant classical and contemporary sources. The results show that each caliph had a unique contribution: Abu Bakr as-Shiddiq emphasized the preservation of the Qur'an, Umar bin Khattab developed the educational administration system and teacher deployment; Uthman bin Affan perfected the codification of the Qur'an as an educational standard; and Ali bin Abi Thalib strengthened moral education and critical reasoning. These findings show that the Islamic education system during the Khulafaur Rasyidin era emphasized the integration of spiritual, intellectual, and moral values. The main argument of this research is that the educational model developed during that period can be used as a basis for strengthening the madrasa curriculum which is oriented towards the formation of Islamic character and leadership which is adaptive to the changing times